Human brucellosis in febrile patients seeking treatment at remote hospitals, northeastern Kenya, 2014–2015 - Njeru, J.; Melzer, F.; Wareth, G.; El-Adawy, H.; Henning, K.; Pletz, M.W.; Heller, R.; Kariuki, S.; Fèvre, Eric M.; Neubauer, H. (Centers for Disease Control and Prevention, 2016)
During 2014–2015, patients in northeastern Kenya were assessed for brucellosis and characteristics that might help clinicians identify brucellosis. Among 146 confirmed brucellosis patients, 29 (20%) had negative serologic tests. No clinical feature was a good indicator of infection, which was associated with animal contact and drinking raw milk.